2020
DOI: 10.1016/j.apergo.2019.102968
|View full text |Cite
|
Sign up to set email alerts
|

Inter-individual variability in load carriage economy and comparisons between different load conditions

Abstract: The Leeds Beckett repository holds a wide range of publications, each of which has been checked for copyright and the relevant embargo period has been applied by the Research Services team. We operate on a standard take-down policy. If you are the author or publisher of an output and you would like it removed from the repository, please contact us and we will investigate on a case-by-case basis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
4
2
Order By: Relevance
“…Nonetheless, and remarkably, despite the characteristics related to load size, speed, and expertise that the 8 studies reporting the Free-Ride have in common, the analysis of the 45 studies shows that none of these aspects influence the probability to find Free-Ride or not (p value >.05) (Table 1). Either way, even when our main results do not support a general Free-Ride capacity, many authors (Abe et al, 2008b;Falola et al, 2000;Hudson et al, 2020Hudson et al, , 2021Kramer, 2003;Pal et al, 2014;Soule et al, 1978;Vickery-Howe et al, 2021;Watson et al, 2008) recognize that some of the participants in similar experiments were able to carry loads very economically under certain conditions. Therefore, many researchers highlight the high individual variability, affecting the costs of both loaded and unloaded trials (de Mendonça & Pereira, 2008;Heglund et al, 1995;Hudson et al, 2020;Kramer, 2010;Rue & Kramer, 2017;Vidal-Cordasco et al, 2021), were some individuals decrease their locomotion costs for some burdened trials, whereas other subjects increase their costs of locomotion when the load is increased.…”
Section: Discussioncontrasting
confidence: 66%
See 3 more Smart Citations
“…Nonetheless, and remarkably, despite the characteristics related to load size, speed, and expertise that the 8 studies reporting the Free-Ride have in common, the analysis of the 45 studies shows that none of these aspects influence the probability to find Free-Ride or not (p value >.05) (Table 1). Either way, even when our main results do not support a general Free-Ride capacity, many authors (Abe et al, 2008b;Falola et al, 2000;Hudson et al, 2020Hudson et al, , 2021Kramer, 2003;Pal et al, 2014;Soule et al, 1978;Vickery-Howe et al, 2021;Watson et al, 2008) recognize that some of the participants in similar experiments were able to carry loads very economically under certain conditions. Therefore, many researchers highlight the high individual variability, affecting the costs of both loaded and unloaded trials (de Mendonça & Pereira, 2008;Heglund et al, 1995;Hudson et al, 2020;Kramer, 2010;Rue & Kramer, 2017;Vidal-Cordasco et al, 2021), were some individuals decrease their locomotion costs for some burdened trials, whereas other subjects increase their costs of locomotion when the load is increased.…”
Section: Discussioncontrasting
confidence: 66%
“…Thus, experience, especially at a high level of training, maybe also an important factor to consider for future experimental designs. However, many others considering also highly experienced carriers disagree with this assumption (Grenier et al, 2012; Hudson et al, 2020; Lloyd et al, 2011; Lloyd, Parr, Davies, & Cooke, 2010; Pal et al, 2014), and according to this review, the possibility to find a Free‐Ride capacity in the literature is not related with the interaction between the experience of the carriers and the load position, neither between the experience of the carriers and the load size (Table S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The extra weight or mass added to the chest wall, as in obesity condition, causes a compression of the thorax, thus decreasing respiratory compliance and lung volumes (Wang and Cerny 2004). As previously observed in healthy and lean subjects, a load on the D r a f t trunk between 15-20% of body weight, as observed in obesity (Hong et al 2008;Hudson et al 2020), causes chest wall restriction with a concomitant increase in work of breathing and Cw (Faghy et al 2016;Faghy and Brown 2014;Phillips et al 2016). Therefore, previous studies showed that a 12-week diet and physical activity program, induced BM loss and reduction of trunk FM, which significantly enhanced breathing mechanics in men and women with obesity (Babb et al 2011;Bhammar et al 2016).…”
Section: R a F Tmentioning
confidence: 68%